The Adoption of Cloud Computing in Syrian Business Organizations: A TOE Framework Approach - Bahna, Miriam; Szalay, Zsigmond Gábor (Acta Carolus Robertus, 2025)
Cloud-based applications are receiving increasing attention among Syrian companies today. Primarily, companies operating in the technology sector, such as software development companies and system administrators, are those that use and provide cloud-based services, but other sectors, such as banks and insurance companies in the financial sector for financial transaction management, telecommunications companies for database management, and the healthcare sector for electronic records. Cost-effectiveness, scalability and flexibility are valued in the applications. Despite the increased spread, not all companies have been able to provide the necessary environmental, infrastructural, and organizational factors for the adoption and integration of cloud services. The purpose of this paper is to examine the use and acceptance from the users’ viewpoint, primarily from an organizational perspective. For this, a questionnaire-based survey was conducted, and a sample of 400 employees working at companies in Syria was asked about their experiences and opinions regarding the use of cloud services. The results of the research confirm that cloud-based services are relatively widely used, and users cite faster work, efficiency and cost reduction as recognized and accepted benefits, but security concerns still arise.